Molecular cloning of partial and full length of human periostin gene into expression construct - Aziana, Binti Abu Hassan. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Periostin which originally named as the osteoblast-specific factor 2 is highly homologous to jJigH3, a molecule induced by transfonning growth factor (TGF) -131; andfasciclin 1 an insect adhesion molecule. Penostin was proved to play an essential role in promoting the growth of tumor cells. Functional studies of human periostin should be perfonned to intensively understand the function and expression of periostin in nonnal and cancer tissues. In this report, cDNA fragments of periostin from human nonnal colon total RNA are isolated by R T -PCR for the purpose of amplification of the gene fragments, clone into pTargeT™ Mammalian Expression Vector System and sent to DNA sequencing analysis. Infonnation generated from DNA sequencing analysis is used to confinn the successful construction of the periostin into expression vector. Expression constructed ofperiostin into pTargeT™ vector can be used to begin functional studies of penostin inside mammalian cell lines system. The partial fragment of penostin gene with a predicted size of 685 bp was successfully amplified. However subcloned of periostin in pTargeTTM vector was unsuccessful due to several problems. Therefore, DNA sequencing analysis was not perfonn.